ITK tunes IL-4-induced development of innate memory CD8(+) T cells in a γδ T and invariant NKT cell-independent manner - Huang, Weishan (Society for Leukocyte Biology, 2014)
True memory CD8(+) T cells develop post antigenic exposure and can provide life-long immune protection. More recently, other types of memory CD8(+) T cells have been described, such as the memory-like CD8(+) T cells (IMP; CD44(hi)CD122(+)) that arise spontaneously in Itk(−/−) mice, which are suggested to develop as a result of IL-4 secreted by NKT-like γδ T or PLZF(+) NKT cells found in Itk(−/−) mice. However, we report here that whereas IMP CD8(+) T cell development in Itk(−/−) mice is dependent on IL-4/STAT6 signaling, it is not dependent on any γδ T or iNKT cells. Our experiments suggest that the IMP develops as a result of tuning of the CD8(+) T cell response to exogenous IL-4 and TCR triggering by ITK and challenge the current model of IMP CD8(+) T cell development as a result of NKT-like γδ T or iNKT cells. These findings suggest that some naive CD8(+) T cells may be preprogrammed by weak homeostatic TCR signals in the presence of IL-4 to become memory phenotype cells with the ability to elaborate effector function rapidly. The role of ITK in this process suggests a mechanism by which IMP CD8(+) T cells can be generated rapidly in response to infection.